8 - US Foreign Policy under President Barack Obama and the Promotion of Multilateralism and the Rule of Law - Mangu, André Mbata (Africa Development, 2021)
Five years ago, in November 2008, Barack Hussein Obama was elected the 44th US president. Senator Obama’s campaign message had been ‘change’, ‘change we need’, and ‘change we should believe in’. In this post-Cold War era, the US is the only remaining superpower and the American president the world’s most influential leader. Accordingly, despite the fact that non-Americans do not participate in an American presidential election, they are nevertheless interested in its outcome given the leading role that the US plays in shaping international relations, for better or worse. This article does not explore US politics. Nor does it revisit the political economy of imperialism let alone the dependency discourse. It rather reflects on American foreign policy against the background of the promises that Senator Obama made in his book, The Audacity of Hope and later during the campaign. It is based on the hopes that his election raised in the ‘world beyond the American borders’ and aims to pave the way for a critical but fair assessment of US foreign policy under President Obama.